Questions of modernity - Mitchell, Timothy, 1955- (University of Minnesota Press, 2000)
Modernity has always laid claim to universal certainty--which meant assigning a different and lesser significance to anything deemed purely local, non-Western, or lacking a universal expression. Focusing on the making of modernity outside the West, eight leading anthropologists, historians, and political theorists explore the production of new forms of politics, sensibility, temporality, and selfhood in locations ranging from nineteenth-century Bengal to contemporary Morocco.
Keywords: Developing countries -- Social conditions.; Civilization, Modern.; Developing countries -- Politics and government.; Civilisation moderne et contemporaine.; Pays en voie de développement -- Conditions sociales.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Civilization, Modern; Politics and government; Social conditions; Developing countries